Emerging materials and technologies for advancing bioresorbable surgical meshes - Shiroud Heidari, Behzad; Dodda, Jagan Mohan; El-Khordagui, Labiba K; Focarete, Maria Letizia; Maroti, Peter; Toth, Luca; Pacilio, Serafina; El-Habashy, Salma E; Boateng, Joshua; Catanzano, Ovidio; Sahai, Nitin; Mou, Lingjun; et al. (Acta biomaterialia, 2024)
Surgical meshes play a significant role in the treatment of various medical conditions, such as hernias, pelvic floor issues, guided bone regeneration, and wound healing. To date, commercial surgical meshes are typically made of non-absorbable synthetic polymers, notably polypropylene and polytetrafluoroethylene, which are associated with postoperative complications, such as infections. Biological meshes, based on native tissues, have been employed to overcome such complications, though mechanical strength has been a main disadvantage. The right balance in mechanical and biological performances has been achieved by the advent of bioresorbable meshes. Despite improvements, recurrence of clinical complications associated with surgical meshes raises significant concerns regarding the technical adequacy of current materials and designs, pointing to a crucial need for further development. To this end, current research focuses on the design of meshes capable of biomimicking native tissue and facilitating the healing process without post-operative complications. Researchers are actively investigating advanced bioresorbable materials, both synthetic polymers and natural biopolymers, while also exploring the performance of therapeutic agents, surface modification methods and advanced manufacturing technologies such as 4D printing. This review seeks to evaluate emerging biomaterials and technologies for enhancing the performance and clinical applicability of the next-generation surgical meshes. STATEMENT OF SIGNIFICANCE: In the ever-transforming landscape of regenerative medicine, the embracing of engineered bioabsorbable surgical meshes stands as a key milestone in addressing persistent challenges and complications associated with existing treatments. The urgency to move beyond conventional non-absorbable meshes, fraught with post-surgery complications, emphasises the necessity of using advanced biomaterials for engineered tissue regeneration. This review critically examines the growing field of absorbable surgical meshes, considering their potential to transform clinical practice. By strategically combining mechanical strength with bioresorbable characteristics, these innovative meshes hold the promise of mitigating complications and improving patient outcomes across diverse medical applications. As we navigate the complexities of modern medicine, this exploration of engineered absorbable meshes emerges as a promising approach, offering an overall perspective on biomaterials, technologies, and strategies adopted to redefine the future of surgical meshes.
Keywords: Humans; chirurgické síťky; Biopolymers; vstřebatelné implantáty; 4D printing; zvířata; Wound healing; Surgical meshes; Biocompatible Materials; Hydrogels; Bone regeneration; Animals; Clinical complications; biokompatibilní materiály; Surgical Mesh; lidé; Absorbable Implants; Hernia